Improving Mechanical Properties of Recycled Aggregate Pervious Concrete Using Taguchi Method - Hemeda Eslam S.; Bashandy Alaa A.; Nasser Amal A. (Civil and Environmental Engineering)
The construction demolition is non-degradable. Recycled aggregates were utilized to create sustainable products in pervious concrete manufacture. Adding fibers enhances pervious concrete mechanical properties. High absorption of Recycled aggregate (RA) and polyethylene-glycol are used to ensure internal curing. The purpose of this study was to statistically improve the mechanical properties of pervious concrete based on an experimental investigation. Taguchi method was employed to present DOE (Design of Experiment). Five factors in four levels designed by Taguchi provide sixteen mixes (L16 array). The factors were the replacement of coarse aggregates by recycled aggregates, W/C ratio, synthetic macro-fiber, steel fiber and polyethylene-glycol. Designed mixes were prepared. Taguchi’s analysis concluded; that macro-fiber addition has no impact on mechanical properties. Using a ratio of 10% recycled aggregates replacement was the optimum ratio. Taguchi prediction of optimum mixes was experimented with using mixes. Confirmation test results agree with the predicted values within ±10%.